Equilibrium, Kinetic and Mechanistic Studies of Formation of Cis- mono (AA)bis (oxaJato) Chromate (III) C,omplex (where AA is Â· glycine, alanine and histidine)In Monderately Aqueous Acidic Solution - Abdullah, M.A.; iz, B.K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Equilrium, kinetic and mechanistic studies for thcoordination of ; some amino acids "'AA'1 glycine, alanine, .a:ncl histidine, to Cr (Ill) center of trans .[Cr(ox}2(B.2 0hr TJ' cornplein monderarely acidicrange ofpH=4.8-6-.7 ( p =Q.4M NaN03) are reported. The equili riumc.onsta:nts at 25Â°C .were found logKequ.=4.95J ,5.206and5.128for glycine, alap.ine, md histidine, ligation. reactions respectively.. The substitution reaction is kinetically involve rwo parallel complex reactions, each inch,tdes there difierent e_onsecutive steps of differentÂ· species of Ct(III). The reactant, Ti, branches through byrolysis into, doubly charged anion, conjugated se of trans[Cr(ox)22(H0)0Hr2whlch inleracts with (AAH) to from outer-sphere complex, that is followed by interchange reaction of one molecule H20 with one end of AA- ron from an active intermediate species of transÂ [Cr(Qx)2(AA)OHT3 which cbanges to final product ; c.isÂ [Cr(ox}1(AA)J?. While the remai ning part of reactant interacts alsowith zwitter i:on (AAH) on other side to form another outer-sphere.complex which also undergaes interchange reaction of one molecule H10 wHh AA- ion to ive twoÂ· active intennediates species, trans and cis-[Cr(ox)2(AA)H2 or, whlch later convert tp the same prodÂ·uct .; cisÂfCr(ox)z(AA)]2-. TI1e interchange rate co.nstant of transÂ [Cr(ox)2(AA)OH] formation relatively appears much larger than (A H*=8.8kc 1/n1ol) that of ds[Cr(.oxh AA)H:z Ot formation( l\ H*Â·=14.0Kca l/mol), wbile the latter rate constant'is oeaily (5-10)time l(!I'ger than that oftrans-{Cr(ox)2(AA)H20t fennatlon